Memanfaatkan Fungsi Sistem Informasi Manajemen: Prospek dan Tantangan di Dunia Bisnis - Samosir, Refani Abednego; Jhon Kristopel Manalu; Darwis Manalu (CV. KAMPUS AKADEMIK PUBLISING, 2026)
In the rapidly evolving digital era, Management Information Systems (MIS) have become an essential component in business strategy and operational activities. This research focuses on the evolution of the role of MIS from a data processing tool to a strategic catalyst that transforms business models and enhances organizational interaction with customers and competitors. Recognizing the importance of MIS in a competitive business environment, this study explores how MIS can be leveraged for innovation and differentiation, while addressing challenges such as data security, system integration, and employee training needs. This research employs an industry survey method and in-depth interviews with practitioners to gain a comprehensive perspective on the implementation and challenges of MIS. The main objectives of this study are to assess how MIS can be used to support strategic business decisions and operations, as well as to identify and address emerging challenges in its application. The results of this study are expected to provide practical guidance for business leaders and IT practitioners, as well as theoretical contributions to the academic literature on the application of MIS in a dynamic business environment. This approach enables the research to not only identify the utility of MIS in supporting strategic business decisions and operations but also to highlight how MIS contributes to innovation and differentiation in a competitive business landscape.